1990
DOI: 10.1161/01.res.66.5.1436
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-mediated microvascular dysfunction in postischemic canine skeletal muscle. Role of granulocyte adherence.

Abstract: Recent studies implicate a role for granulocytes in the genesis of the microvascular and parenchymal cell dysfunction, which occurs upon reperfusion of ischemic tissues. Although the molecular mechanisms underlying this neutrophil-mediated injury are not completely understood, it is clear that an essential first step in granulocyte migration from the vascular lumen to the interstitial space is adherence to vascular endothelium. The purpose of this study was to determine whether prevention of neutrophil adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(98 citation statements)
references
References 31 publications
3
93
0
2
Order By: Relevance
“…37,38 A strong argument that supports this hypothesis are the neutrophil depletion or CD11/CD18 blocking experiments that have been shown to attenuate vascular injury under inflammatory and ischemia-reperfusion conditions. [38][39][40][41] However, when microvascular permeability was measured simultaneously with leukocyte-endothelial interactions, local plasma leakage sites were distinct from those of leukocyte adhesion or transmigration. 4,5,[42][43][44][45] Moreover, several studies have shown that the timing of leukocyte adhesion and transmigration are not well correlated with the evoked permeability change during acute inflammation.…”
Section: Leukocyte Extravasation and Vascular Permeabilitymentioning
confidence: 99%
“…37,38 A strong argument that supports this hypothesis are the neutrophil depletion or CD11/CD18 blocking experiments that have been shown to attenuate vascular injury under inflammatory and ischemia-reperfusion conditions. [38][39][40][41] However, when microvascular permeability was measured simultaneously with leukocyte-endothelial interactions, local plasma leakage sites were distinct from those of leukocyte adhesion or transmigration. 4,5,[42][43][44][45] Moreover, several studies have shown that the timing of leukocyte adhesion and transmigration are not well correlated with the evoked permeability change during acute inflammation.…”
Section: Leukocyte Extravasation and Vascular Permeabilitymentioning
confidence: 99%
“…However, the ability of neutrophils and macrophages to induce injury in other cells in vitro [10][11][12] suggests that these early stages of muscle inflammation may also involve damage to muscle fibers caused by the invading cells. This possibility is supported by the ability of neutrophils to induce skeletal muscle injury during tissue reperfusion after ischemia [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…When activated, PMNs increase in size and stiffness, which facilitates their trapping in alveolar capillaries and precapillary vessels (14,40,41). This may contribute to the no-reflow phenomenon, wherein a tissue fails to reperfuse despite restoration of adequate perfusion pressures (42)(43)(44). Current optimal clinical pulmonary preservation strategies, which consist of hypothermic lung storage in an electrolyte solution with no form of reperfusion therapy (45), miss the chance to mitigate deleterious PMN-endothelial adhesive interactions.…”
Section: Discussionmentioning
confidence: 99%